Cover Image, Volume 4, Number 4, June 2022. Issue 4 (13th July 2022) - Xia, Chengkai; Surendran, Subramani; Ji, Seulgi; Kim, Dohun; Chae, Yujin; Kim, Jaekyum; Je, Minyeong; Han, Mi‐Kyung; Choe, Woo‐Seok; Choi, Chang Hyuck; Choi, Heechae; Kim, Jung Kyu; et al.
Abstract : Front cover image : Discovering the creative multifunctional potential of a single material is an essential criterion for formulating highly efficient energy storage and conversion systems. In article number 10.1002/cey2.207, Uk Sim and co‐workers report the development of sulfur self‐doped biochar (SA‐Came) derived from the Camellia Japonica flowers as a multifunctional electrode for overall water splitting and supercapacitor application.